Sports courts in conditions of proper use in Brazil: influence on teaching-learning in Physical Education classes (2015) (Research, Society and Development, 2020)
The area of education has undergone several changes over time, and along with it, Physical Education. School Physical Education aims to cultivate pedagogical reflections. The lack or low quality of a sports court can have negative effects on the Physical Education class. The objective of this work is to show the rates of sports courts in conditions of proper use in Brazil in 2015, and their influence on teaching-learning in physical education classes. The approach of this study is qualitative, with a subtle quantitative bias, without recurrence to rigid statistical methods. The quantitative research was carried out with the database of the Brazilian Institute of Geography and Statistics - IBGE. The results show that private schools have a higher rate of sports courts in adequate conditions of use than public schools. The sports court suitable for use at school is of great importance for the teaching-learning process in physical education classes. Through a court with an adequate infrastructure, the student has the opportunity to experience other bodily manifestations, thus, making the student have a vision of the whole in relation to the body culture created by man.